Изучение стратиграфии херсонесского городища - Стржелецкий, С.Ф. (Археологія, 2007)
Статья посвящена истории развития стратиграфических исследований Херсонеса Таврического на основе усовершенствования методики ведения раскопок. У статті розглянуто історію вдосконалення методики археологічних розкопок у Херсонесі Таврійському. Простежено хронологію виділення археологічних шарів та історію їх дослідження. Окреслено стан і перспективи вивчення стратиграфії до початку розкопок 1963 р. The article views the history of improvement of the methods of archaeological excavations in Tauric Chersonesos. Based
on that, the chronology of allotment of archaeological layers, and the history of their research are traced. The state and
the perspectives of study the stratigraphy at the moment of the beginning of excavations in 1963 are determined.